2010
DOI: 10.1007/s00296-010-1412-7
|View full text |Cite
|
Sign up to set email alerts
|

Can fibromyalgia be associated with whiplash injury? A 3-year follow-up study

Abstract: The objective of this study is to assess the long-term outcome and natural history of a cohort of patients with whiplash injury regarding the development of fibromyalgia. Of the 153 patients who were admitted to the emergency room after whiplash injury in 2004, 126 were reassessed 3 years later. Also, 33 of 53 patients from the original control group of hospitalized patients with fractures were reevaluated. Patients were interviewed by phone and by written forms using a detailed questionnaire. Patients who com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
0
16
0
1
Order By: Relevance
“…Recently Tishler et al, [19] published a 3-year prospective cohort study following the original individuals in the Tishler et al study who had WL following an MVC. These investigators reported a 2.5% prevalence of FM [19], no higher than the established prevalence of FM noted in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently Tishler et al, [19] published a 3-year prospective cohort study following the original individuals in the Tishler et al study who had WL following an MVC. These investigators reported a 2.5% prevalence of FM [19], no higher than the established prevalence of FM noted in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…These investigators reported a 2.5% prevalence of FM [19], no higher than the established prevalence of FM noted in the general population. On the surface, it might seem that our results fall somewhere between the estimates cited previously by Buskila et al [4] and Tishler et al [19, 20]. However, these studies contain limitations that raise concerns about the validity of the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies from the United Kingdom have linked motor vehicle accidents, but not workplace injuries, with onset of diffuse pain, with poorer general health and psychological status in the pre-accident phase recorded as important predisposing factors 13,14 . Therefore, reports relating injury to causation in FM, mostly following whiplash injury, both support and refute the association of localized injury and diffuse pain 16,17,18 . Therefore, reports relating injury to causation in FM, mostly following whiplash injury, both support and refute the association of localized injury and diffuse pain 16,17,18 .…”
Section: Discussionmentioning
confidence: 97%
“…In their review of Tishler, et al 7,8 , the authors forgot to mention that the majority of the patients were male, in contrast to the expected sex distribution in FM. Only 0.6% of the study group developed FM, far below the expected prevalence of FM in the general population, suggesting a protective role for neck injury in FM.…”
Section: To the Editormentioning
confidence: 97%